Certain Considerations on the Right to Legal Assistance in Civil Trials - CREÅ¢Daniela Cristina (Journal of Legal Studies, 2017)
Ensuring access to justice for all litigants, whether individuals or legal persons, and the operation of the principle of equality for parties in a civil trial, involves, among other things, providing appropriate legal assistance, including by granting certain exemptions, reductions, or postponements in the payment of legal fees stipulated by law to those who do not have the financial resources to initiate and sustain a civil trial. Throughout the following we shall emphasise certain aspects of the right to legal assistance, as seen from the perspective of both domestic legislation, and certain European documents.